2021
DOI: 10.1177/20417314211021220
|View full text |Cite
|
Sign up to set email alerts
|

Development of a library of laminin-mimetic peptide hydrogels for control of nucleus pulposus cell behaviors

Abstract: The nucleus pulposus (NP) of the intervertebral disc plays a critical role in distributing mechanical loads to the axial skeleton. Alterations in NP cells and, consequently, NP matrix are some of the earliest changes in the development of disc degeneration. Previous studies demonstrated a role for laminin-presenting biomaterials in promoting a healthy phenotype for human NP cells from degenerated tissue. Here we investigate the use of laminin-mimetic peptides presented individually or in combination on a poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 108 publications
(208 reference statements)
0
7
0
Order By: Relevance
“…[ 75 ] Laminins are ECM glycoproteins comprise of β , α , and γ chains that regulate cell survival, adhesion, differentiation, and migration. A study reported that a series of laminin‐mimetic peptide poly(ethylene) glycol (PEG) hydrogels modulated integrin and syndecan binding in NP cells, thus promoting ECM biosynthesis [ 76 ] primarily through integrin α 3 mediated interaction with laminin, which also associated with phosphorylation of signaling molecules of extracellular‐signal‐regulated kinase (ERK1/2) and glycogen synthase kinase (GSK3 β ). [ 77 ]…”
Section: Rationale Precision Biomaterial‐based Tissue Engineering Tar...mentioning
confidence: 99%
“…[ 75 ] Laminins are ECM glycoproteins comprise of β , α , and γ chains that regulate cell survival, adhesion, differentiation, and migration. A study reported that a series of laminin‐mimetic peptide poly(ethylene) glycol (PEG) hydrogels modulated integrin and syndecan binding in NP cells, thus promoting ECM biosynthesis [ 76 ] primarily through integrin α 3 mediated interaction with laminin, which also associated with phosphorylation of signaling molecules of extracellular‐signal‐regulated kinase (ERK1/2) and glycogen synthase kinase (GSK3 β ). [ 77 ]…”
Section: Rationale Precision Biomaterial‐based Tissue Engineering Tar...mentioning
confidence: 99%
“…At least six integrin-and syndecan-binding peptide sequences have been developed which successfully drive healthier NP cell phenotypes [132]. The use of such systems provides the clearest indication yet that matrix cues can be used to directly modulate cell behaviours [185] and potentially mimic a combination of cues present in development, health, and degeneration. Peptide-conjugated alginate hydrogels have similarly been exploited, with cell-adhesive and syndecan-binding domains encouraging the production of NP-specific phenotypes within alginate cultures, in some instances regardless of presented cell-adhesive domains [186].…”
Section: Development Of Biomimetic Systems For the Delivery Of Matrix...mentioning
confidence: 99%
“…Nor are there many that combine the use of these matrix molecules with stiffness-tuneable biomaterials for mechanical cue incorporation. This has been achieved in a small number of instances for IVD, using in situ crosslinkable peptide delivery systems [244,245] and laminin-functionalised pegylated hydrogels of varying stiffnesses [185]. Such approaches are generating novel data regarding mechanotransduction, notochord morphogenesis, intracellular signalling, cell differentiation, and matrix synthesis, which are of major relevance to IVD regeneration strategies moving forward [81,132].…”
Section: Gag Mimicmentioning
confidence: 99%
“…Bioadhesive ligands such as full-length proteins or short peptides have been shown to functionalize biomaterials to promote cell adhesion and modulate cell behavior. The utilization of short peptides showed a number of apparent advantages: small peptides are more stable, cheaper, and capable of mass production . Full-length laminin proteins have multiple bioactive amino acid sequences that may lead to uncontrollable intercellular interactions . IKVAV and YIGSR are laminin-mimetic peptides located in the Laminin α1 and β1 chains, respectively.…”
Section: Introductionmentioning
confidence: 99%